PELAKSANAAN STANDAR PELAYANAN PAJAK KENDARAAN BERMOTOR DI KANTOR BERSAMA SAMSAT UPT KUTAI KARTANEGARA - Surya Adi Praja (Jurnal Administrative Reform, 2017)
This paper tried to explain the implementation of the standard service of vehicles tax at Kutai Kartanegara Samsat Office. Based on the observation made, it was found that the six standard service of vehicles tax that include: system, mechanism and procedure, service time, fee/tariff, service product and complaint management were generally implemented according to the expected result.